Motivational Factors for Women Employment in Vyas Municipality of Tanahu District, Nepal - Rimal, Ranju; Pasa, Rajan Binayek (Nepalese Journal of Development and Rural Studies, 2018)
This study explains motivational/de-motivational factors for women employment from rural development standpoint. In doing so, quantitative approach and case study research design have been applied. The numeric data are collected from 72 respondents whereas narrative information are generated from five participants selected form five government and five non-government institutions of Vyas Municipality of Tanahu District. In this stance, anonymous self administered questionnaires and key informant interview techniques are applied. The result shows that motivational factors (i.e. salary, bonus, security, safety promotion) are encouraging women to perform their duty/responsibility effectively and efficiently with honorable way. They are not only supporting to their family livelihood but also playing gender role (social, economic & political roles) in community and society. However, some of the respondents are also experiencing less paid salary, sexual harassment, physical difficulties at the time of menstruation and not sufficient maternity leave (de-motivational factors). De-motivated women are failed to join in higher education and unable to perform gender role for rural development. Thus, better to address de-motivational factors by the local development stakeholders including aged persons supporting deeply rooted patriarchal systems of Hindu culture for motivating women for employment.